Diagnostic Application of Multidetector-Row Computed Tomographic Coronary Angiography to Assess Coronary Abnormalities in Pediatric Patients: Comparison With Invasive Coronary Angiography - Chien-Chang Juan; Betau Hwang; Pi-Chang Lee; Chun-Chang Laura Meng (Pediatrics and Neonatology)
Multidetector-row computed tomographic (MDCT) coronary angiography has been validated for noninvasive assessment of coronary anatomy. However, we have less experience in diagnosing children with congenital or acquired coronary artery abnormalities by MDCT. We compared the results of MDCT with invasive coronary angiography (ICA) on identifying coronary abnormalities in infants, children, and adolescents with coronary artery abnormalities, including aneurysm, coronary fistula, or anomalous left coronary artery from pulmonary artery (ALCAPA). Methods: From January 2002 to December 2009, patients with congenital or acquired coronary abnormalities underwent either ICA, MDCT, or both studies for assessment of coronary anatomy. We reviewed all patients’ clinical diagnosis, coronary abnormalities identified by MDCT or ICA, and analyzed the advantages and disadvantages between those two methods. Results: Thirty-three patients (20 males and 13 females) with a mean age of 10.3 years (range: 18 days to 25 years) had coronary abnormalities, including coronary artery aneurysm in Kawasaki disease (n=15), coronary artery fistula (n=12), myocardial bridge (n=2), and ALCAPA (n=4). In 17 patients only referred for ICA, 5 coronary aneurysms (3 on left main coronary artery, 1 on left anterior descending artery segment proximal, 1 on right coronary artery segment proximal), 11 coronary artery fistulas, and 2 ALCAPAs were detected. Sixteen patients received MDCT study, and 14 coronary artery aneurysms (4 on right coronary artery, 5 on left main coronary artery, 4 on left anterior descending artery, 1 on left circumflex artery), 3 myocardial bridges, 1 coronary artery fistulas, and 2 ALCAPAs were assessed. Ten patients with Kawasaki disease-related coronary lesions received MDCT study, and totally 102 (78.5%) segments permitted visualization with accurate diagnostic image quality. In this study, there were 11 patients with indication for conventional ICA spared invasive angiography after precise assessment by MDCT. Conclusion: We conclude that MDCT is a good and useful modality for assessment of congenital or acquired coronary abnormalities in pediatric patients. However, MDCT cannot replace invasive cardiac catheterization and ICA because of lack of therapeutic role.